A Factor Decomposition on China's Carbon Emission from 1997 to 2012 Based on IPAT-LMDI Model. (26th May 2015) - Li, Wei; Shen, Ya-Bo; Zhang, Hui-Xia
Abstract : We probe into the key factors that possess significant effects on China's CO2 emissions during 1997–2012 on the basis of IPAT-LMDI model. Carbon dioxide emissions are specifically decomposed into CO2 emission intensity, energy structure, energy intensity, industrial structure, economic output, and population scale effects. Results indicate that the paramount driving factors that resulted in the growth of CO2 emissions are economic output, population scale, and energy structure. In contrast, energy intensity and industrial structure generally play an outstanding role in reducing emissions. This paper constructs a new weight assessment system by introducing "contribution value-significant factor-effect coefficient" to replace "contribution value-contribution rate" in the previous literature. According to the most significant positive effect and the most negative effect from the conclusion, we point out the effective policies that can not only accelerate the target of "China's carbon emissions per unit of GDP could be cut down by 40–45% by 2020, from 2005 levels, " but also have crucial significance on the low-carbon economic development strategy of China.